The Status of the Covernote and the Role of the Notary in Banking - I Made Pria Dharasana; Indrasari Kresnadjaja; I Putu Lingga Dhananjaya (Law Doctoral Community Service Journal, 2023)
Covernotes are customary or customary law in the banking industry, and they are regarded as having legal force that is binding on the parties. When completing the authentic deed made by a notary, the covernote is used as a condition in the credit application process but serves as a temporary guarantee. The aim of this research is to know the the status of the covernote and the role of the notary in banking. This type of research approach uses normative juridical type of research. The approach used by the authors in this thesis, namely by the approach of legislation (of approach), a case approach (of approaches). Conceptual approach (conseptual approach). The result shows that whether laws and regulations are effective or not cannot stand alone but has a reciprocal relationship in society. And the law in a society will be effective because it is supported by a culture of the society that obeys and obeys the law. The government has regulated the provisions both embodied in laws and regulations. Therefore, all parties can carry out all existing rules as they should.